Description of a new species of Cosmocerca Diesing, 1861 (Nematoda: Cosmocercidae) in Hoplobatrachus crassus (Jerdon, 1853) (Anura: Dicroglossidae) from Asansol coal-field area, West Bengal, India - Banerjee, Siddharthasankar; Sou, Sujan Kumar (Zootaxa, 2020)
A new cosmocercid nematode species, Cosmocerca asansolensis sp. nov. (Ascaridida, Cosmocercidae) is described from an Indian bullfrog, Hoplobatrachus crassus (Jerdon, 1853), from Asansol town, Paschim Bardhaman district, West Bengal, India. This species is characterized by the presence of five pairs of plectanes supporting preanal papillae, absence of somatic papillae in females, and having one pair large postanal papillae, a single papilla on the upper lip of cloaca, a single papilla on the lower lip of cloaca and one pair adanal papillae in males and one pair postanal papillae in females. Spicules of the present species are equal, moderately sclerotized, knobbed and wide proximal end gradually tapering to a fine point distally. The gubernaculum is well sclerotized and Y-shaped. Cosmocerca asansolensis sp. nov. represents the 33rd species assigned to the genus, 8th from Oriental region and 6th species from India.